2023
DOI: 10.1186/s10194-023-01556-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting response to CGRP-monoclonal antibodies in patients with migraine in Japan: a single-centre retrospective observational study

Abstract: Background Anti-calcitonin gene-related peptide monoclonal antibodies (CGRPmAbs) are a favourable option for patients with migraine who experience distressful headache disability and fail to respond to traditional preventive treatment options. However, since CGRPmAb has been available for only 2 years in Japan, the difference between good and poor responders remains unknown. We aimed to investigate the clinical characteristics of patients with migraine in Japan who responded well to CGRPmAb bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 31 publications
1
25
0
1
Order By: Relevance
“…The REFORM study's clinical deep phenotyping allows for exploration of clinical predictors for efficacy of erenumab, as well as treatment-induced biomarker changes and patterns in migraine and its subtypes. Previous studies have proposed several positive predictors of treatment response to mAbs against CGRP signaling, including unilateral pain localization [ 32 , 36 , 37 ], response to triptans [ 32 , 38 , 39 ], shorter duration of MOH [ 32 , 40 , 41 ], and older age [ 42 ]. In contrast, poor response has been associated with anxiety disorders and a higher number of failed preventive medications [ 34 , 40 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The REFORM study's clinical deep phenotyping allows for exploration of clinical predictors for efficacy of erenumab, as well as treatment-induced biomarker changes and patterns in migraine and its subtypes. Previous studies have proposed several positive predictors of treatment response to mAbs against CGRP signaling, including unilateral pain localization [ 32 , 36 , 37 ], response to triptans [ 32 , 38 , 39 ], shorter duration of MOH [ 32 , 40 , 41 ], and older age [ 42 ]. In contrast, poor response has been associated with anxiety disorders and a higher number of failed preventive medications [ 34 , 40 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous real-world studies evaluating two or more types of CGRP mAbs with three to six-month follow-up showed ≥50% response rates of 48.5–56.3% at three months (14,1820) and 35.4–64.9% at six months (14,18,20). These response rates were comparable to those in the present study.…”
Section: Discussionmentioning
confidence: 93%
“…In a study of 260 patients with migraine receiving CGRP mAbs, typical migraine characteristics such as unilateral localization, pulsating character, photophobia or nausea were associated with ≥75% responders at three months, while CM, MOH, and concomitant depression were related to nonresponders (22). Older age, lower MMDs and fewer previous treatment failures were also associated with >50% responders at three months in a real-world study (19). Similar to previous studies, unilateral localization, pulsatile nature (18,22), less comorbid MOH (22), fewer prophylactics used previously, and fewer baseline MMDs (19) were related to responders in our study.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations